CANCER EN CUIRASSE - Kakakhel, Khadimullah; Saeed, A. Karim (Journal of Ayub Medical College Abbottabad, 1988)
Abstract: Skin metastases in the form of cancer en Cuirasse (scirrhous carcinoma) is an uncommon but typical pattern. The primary site may be known or not yet diagnosed. In this form infiltrated, painful, diffuse plagues are observed. A biopsy is mandatory for diagnosis. In the case where biopsy is confirmative and primary site is not found, examination and relevant investigations should be repeated. In minority of cases skin metastases may be the sole secondaries and excision of these along with the primary may give better prognosis. However, excision or radiotherapy may alleviate symptoms.